RURAL MODEL OF INDUSTRIAL DEVELOPMENT IN JAUNPUR DISTRICT AND PLANNING FOR INTEGRATED RURAL DEVELOPMENT: जौनपुर जनपद में औद्योगिक विकास का ग्राम्य प्रतिरूप तथा समन्वित ग्राम्य विकास हेतु नियोजन - Singh, Anamika; Devi, Sujita (International Journal of Research -GRANTHAALAYAH, 2021)
English: The research study area presented is "Rural Development Dynamics in Jaunpur District: A Geographical Study" under the rural model of industrial development and planning for integrated rural development. At present, rural agriculture, rural industry, business employment are the resources of rural development for social, economic, political development in the Indian rural area. India is a country of villages, so for the development of the villages, there is an urgent need for coordinated planning of small and cottage industrial development for rural development. "The glorious point of Jaunpur district from the past is in front of us on the peak of the Sultanate. According to historian Afrikan is not true. Jaunpur city was inhabited since ancient times and had the distinction of being the capital of an ancient Hindu kingdom. The ancient city of Jaunpur was named Javanpur. Ferozeshah Tughlaq laid the foundation of Jaunpur city on the banks of the Gomti River in 1394, in the full memory of his cousin Juna Kha (Mo. Binu Tughlaq), Yavanpur was named after the ancient sage Yamadagni who later converted to Jaunpur, which was renovated by Firoz Shah Tughlaq had. The policy is important for rural development. Hindi: प्रस्तुत शोध अध्ययन क्षेत्र ‘‘ जौनपुर जनपद में ग्राम्य विकास गतिकी: एक भौगोलिक अध्ययन ’’के अन्तर्गत औद्योगिक विकास का ग्राम्य प्रतिरूप तथा समन्वित ग्राम्य विकास हेतु नियोजन का अध्ययन है। वर्तमान समय में भारतीय ग्राम्य क्षेत्र में सामाजिक, आर्थिक, राजनैतिक विकास के लिए ग्राम्य कृषि , ग्राम्य उद्योग , व्यापार रोजगार ग्राम्य विकास का संसाधन है। भारत गॉवों का देश है अतः ग्राम्यों के विकास के लिए लघु एवं कुटीर औद्योगिक विकास का ग्राम्य विकास हेतु समन्वित नियोजन की अति आवश्यकता है। ‘‘ अतीत समय से जौनपुर जनपद गौरवमयी बिन्दुस्पर्शी सल्तनत होने के शिखर पर हमारे सामने है। इतिहासकार अफ्रीक के अनुसार सत्य नहीं है। जौनपुर नगर प्राचीन काल से ही बसा बसाया था और इसे एक प्राचीन हिन्दू राज्य की राजधानी होने का गौरव प्राप्त था। जौनपुर का प्राचीन नगर का नाम जवनपुर था। फिरोजशाह तुगलक अपने चचेरे भाई जूना खा ( मो0 बिनु तुगलक) की पूर्ण स्मृति में गोमती नदी के तट पर जौनपुर नगर की नींव 1394 रखी थी, प्राचीन ऋषि यमदग्नि के नाम पर यवनपुर रखा गया था जो आगे चलकर जौनपुर में परिवर्तित हो गया जिसका जीर्णोद्धार फिरोजशाह तुगलक ने किया था ।[1] आधुनिक समय में ग्रामीण विकास के लिए ग्राम्योद्योग एवं कृषि विकास के संसाधनों का विकास करके ग्राम्य क्षेत्रों में लोगों को शिक्षा के द्वारा समग्र रोजगार का प्रशिक्षण तकनीकी कौशल के माध्यम से ग्रामीण रोजगार उपलब्ध कराकर सम्पूर्ण ग्राम विकास हेतु समन्वित नियोजन की नीति ग्राम्य विकास के लिए महत्वपूर्ण है।